Point-rating system: students' opinion - Elena Yu. Novikova (Moscow Polytechnic University, 2022)
The article touches upon the problems of introduction of a point-rating system for the assessment of an educational process. The author states that the evaluation system must be intelligible and equitable for students. The article presents the results of the students' opinion poll on a point-rating assessment, shows the specificity of approach to the assessment and testing depending on the program specialization, students' progress, study periods.